Single and Combined Effects of Clostridium butyricum and Coccidiosis Vaccine on Growth Performance and the Intestinal Microbiome of Broiler Chickens - Cai, Haiming; Liao, Shenquan; Li, Juan; Liu, Qihong; Luo, Shengjun; Lv, Minna; Lin, Xuhui; Hu, Junjing; Zhang, Jianfei; Qi, Nanshan; Sun, Mingfei (Frontiers in Microbiology, 2022)
Avian coccidiosis is an important intestinal protozoan disease that has caused major economic losses to the poultry industry. Clostridium butyricum can not only maintain the stability of the intestinal barrier, but can also improve the production performance of broiler chickens. We studied the effects of feeding C. butyricum alone, administration of coccidiosis vaccine alone, and the combined administration of C. butyricum and coccidiosis vaccine on body weight gain, feed consumption, and feed conversion ratio of broilers. Meanwhile, intestinal contents of 8- and 15-day-old broilers were collected, and their intestinal microbiome was characterized by high-throughput sequencing of the V3–V4 region of 16S rDNA. We analyzed the oocysts per gram values and lesion scores in the C. butyricum alone group, in a group challenged with the coccidiosis-causing parasite, Eimeria, and in groups simultaneously challenged Eimeria and pretreated with C. butyricum, the coccidiosis vaccine, or combined C. butyricum and coccidiosis vaccine. Intestinal tissue samples were collected from 32-day-old broilers for microbiome analysis. Our results showed that combination of C. butyricum with coccidiosis vaccine significantly improved the performance of broiler chickens and also significantly reduced the oocysts per gram value and intestinal lesions caused by Eimeria sp. infection. Furthermore, C. butyricum and coccidiosis vaccine administered alone or in combination significantly increased the relative abundance of the immune biomarker genus Barnesiella. The significant increase in the abundance of the Clostridia_UCG.014, Eubacterium coprostanoligenes group and Bacteroides was a key factor in controlling Eimeria sp. infection.